OPTICAL AND ELECTRICAL PROPERTIES OF SILICON SOLAR CELLS BY WET CHEMICAL ETCHING - Mauricio Arias; Mackarena Briceño; Aitor Marzo; Antonio Zárate (Journal of the Chilean Chemical Society, 2019)
We present a simple method for the texturing of commercial silicon solar cells in a two-step process by etching in an HF solution containing H2O2. This etching process is facilitated by silver nanoparticles which act as catalytic sites. The etching times for the fabrication of nano-pores on the surface are established. The optical properties of the nano-structures on the surface of silicon solar cell were investigated by spectrometer measurements. The samples presented a total reflection coefficient lower than that of silicon solar cells without the treatment. The global efficiency of the silicon solar cell depends on the chosen preparation conditions for the silver ion concentration, and time of wet etching. The textured surface of solar cells showed an increase in efficiency, with a circuit photocurrent higher than that of a reference silicon solar cell without texturing. The J-V curves of various silicon cells are presented and discussed in correlation with the surface morphology.